Production of fermented cheese whey-based beverage using kefir grains as starter culture : evaluation of morphological and microbial variations - Magalhães, Karina Teixeira (2010)
Whey valorization concerns have led to recent interest on the production of whey beverage simulating kefir. In this study, the structure and microbiota of Brazilian kefir grains and beverages obtained from milk and whole/deproteinised whey was characterized using microscopy and molecular techniques. The aim was to evaluate its stability and possible shift of probiotic bacteria to the beverages. Fluorescence staining in combination with Confocal Laser Scanning Microscopy showed distribution of yeasts in macro-clusters among the grain’s matrix essentially composed of polysaccharides (kefiran) and bacteria. Denaturing gradient gel electrophoresis displayed communities included yeast affiliated to Kluyveromyces marxianus, Saccharomyces cerevisiae, Kazachatania unispora, bacteria affiliated to Lactobacillus kefiranofaciens subsp. Kefirgranum, Lactobacillus kefiranofaciens subsp. Kefiranofaciens and an uncultured bacterium also related to the genus Lactobacillus. A steady structure and dominant microbiota, including probiotic bacteria, was detected in the analyzed kefir beverages and grains. This robustness is determinant for future implementation of whey-based kefir beverages.